2019
DOI: 10.26508/lsa.201800292
|View full text |Cite
|
Sign up to set email alerts
|

Functional inhibition of acid sphingomyelinase disrupts infection by intracellular bacterial pathogens

Abstract: Many intracellular pathogens hijack cholesterol. Inhibiting acid sphingomyelinase alters cholesterol traffic to target different intracellular bacteria, signifying a host-directed approach for treating infectious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…For example, A. phagocytophilum targets flotillins and Neimann-Pick type C1 (NPC1)-bearing vesicles to redirect cholesterol to bacterial inclusions ( Xiong and Rikihisa, 2012 ; Xiong et al, 2019 ). It was also shown that inhibiting cholesterol efflux from lysosomes halts A. phagocytophilum infection, further demonstrating their dependence on host cholesterol ( Cockburn et al, 2019 ).…”
Section: Intracellular Growthmentioning
confidence: 99%
“…For example, A. phagocytophilum targets flotillins and Neimann-Pick type C1 (NPC1)-bearing vesicles to redirect cholesterol to bacterial inclusions ( Xiong and Rikihisa, 2012 ; Xiong et al, 2019 ). It was also shown that inhibiting cholesterol efflux from lysosomes halts A. phagocytophilum infection, further demonstrating their dependence on host cholesterol ( Cockburn et al, 2019 ).…”
Section: Intracellular Growthmentioning
confidence: 99%
“…Endogenous cationic sphingoid bases such as sphingosine and sphinganine inhibit the catabolism of ganglioside GM2 [46], of glucosylceramide [43] at a posttranslational level and presumably also that of SM in ASMD. Many antidepressant drugs such as desipramine and other CADs or synthetic cationic lipids can act as so called "functional inhibitors of ASM" (FIASMAs) [109] (Figure 3A) which is little misleading because it incorrectly implies an ASM specific effect. Due to their physicochemical properties, CADs can easily reach and enter the acidic compartments and accumulate there up to rather high concentrations, thereby significantly increasing the luminal pH value.…”
Section: Activation and Inhibition Of Asmmentioning
confidence: 99%
“…On the other hand, the functional inhibition of ASM activity stops infection cycles of vacuole adapted bacteria such as Anaplasma-phagocytophilum, Chlamydia trachomatis, and Chlamydia pneumoniae or even kills Coxiella burnettii [109,178]. ASM is also an essential regulator of mucosal immunity to enteric pathogens.…”
Section: The Role Of Asm In Bacterial Mycobacterial Fungal and Viral Infectionsmentioning
confidence: 99%
“…Activation of surface receptor (CD95) leads to the translocation of these enzymes from its intracellular location to the sphingomyelin lipid-rich plasma membrane during apoptosis [46,47]. A study by Cockburn et al [48] revealed that mutations in the asmase gene affect the enzyme function, which depletes the efflux of low-density lipoprotein-cholesterol required by vacuole-adapted intracellular pathogens.…”
Section: Role Of Smases In Metabolic Pathwaysmentioning
confidence: 99%